Biotène Versus HydraSmile for Radiation‐Induced Xerostomia: Randomized Double‐Blind Cross‐Over Study - Randall J. Harley; Eve Bowers; Jinhong Li; Mikayla Bisignani; Marci L. Nilsen; Jonas T. Johnson (OTO Open)
Abstract Objective This study aims to compare the effectiveness of 2 artificial saliva substitutes (Biotène vs HydraSmile) in the symptomatic management of radiation‐induced xerostomia. Study Design Randomized double‐blind cross‐over study. Setting Single tertiary care academic institution. Methods Included adult patients ≥6 months postradiotherapy (50‐70 gy) for squamous cell carcinoma of the oral cavity, oropharynx, or larynx. The primary endpoint was change in overall subjective xerostomia score from baseline, through use of HydraSmile versus Biotène. Scores were derived from a 100‐point visual analog scale, with higher scores indicating better symptomatic control. Analysis of covariance model was used to regress the difference in after‐treatment measurement between HydraSmile and Biotène, with respect to baseline differences. Results A total of 91 participants were included (mean age 63.0 years [SD 9.7]; 85.7% male; 97.8% White). Change in overall xerostomia score with respect to baseline was not significantly different between HydraSmile and Biotène (mean difference 1.24, 95% confidence interval [CI] −2.35 to 4.81). Compared to water alone, both HydraSmile (mean difference 7.45, 95% CI 3.61‐11.29) and Biotène (mean difference 7.24, 95% CI 3.06‐11.43) significantly improved overall xerostomia score. Forty (44%) patients reported a preference for Biotène, 46 (50.5%) preferred HydraSmile, and 5 (5.5%) had no preference. Patients who preferred Biotène did not significantly benefit from HydraSmile, whereas those who preferred HydraSmile did not significantly benefit from Biotène. Conclusion Biotène and HydraSmile significantly improved oral dryness among patients with radiation‐induced xerostomia. While neither product demonstrated treatment superiority, individual product preference was predictive of greatest treatment benefit.